Generation of Energy from a Single Fuel Cell Using Synthesized Solid Electrolyte Membrane from Functionalized Polyisoprene/ Carbon Nanotubes - Idibie, C.A.; Awatefe, K.J.; Ogboru, R.O. (Journal of Research Updates in Polymer Science, 2018)
Study on the electrical energy generated from a single fuel cell using a synthesized solid electrolyte membrane from polyisoprene that was impregnated with carbonanotubes was carried out. The initial functionalization of the polymer yielded an ion exchange capacity (IEC) of 4.04, 7.82, 11.1 and 15.53 mmol/g with their corresponding degrees of sulphonation (DS) of 10.93, 21.1, 30.03 and 42.02 %, respectively. The later but highest DS achieved water uptake of 49.23 wt % and proton conductivities of 4.3 x 10-3, 1.2 x 10-3 and 2.6 x 10-2 S/cm for membrane of thickness 250, 215 and 120 mm, respectively. The performance testing of the membrane in a single fuel cell achieved an open circuit voltage (OCV) of 647.23 mV with the synthesised membrane of 35 wt % catalyst loading, 589.79 mV and 410.48 mV of 25 wt % and 15 wt % catalyst loading, respectively at constant DS (42.02 %). Their corresponding power densities achieved were 68.67, 49.20 and 35.83 Mw/cm2, respectively. Thus the functionalization of polyisoprene impregnated with carbon nanotubes through the process of sulphonation with chlorosulphonic acid resulted into the development of solid polymer electrolyte membrane for fuel cell application.